2019
DOI: 10.1021/acs.chemmater.8b03998
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Flow-Driven Aligned Growth of Graphene on Liquid Copper

Abstract: S ingle crystalline graphene (SCG) has proven its potential as an ideal candidate toward high-performance electronic, spintronic, and optoelectronic devices owing to its extremely high intrinsic carrier mobility and significantly wavelengthindependent absorption. 1−4 By chemical vapor deposition (CVD), large-area SCG can be controllably prepared, which is promising to fulfill the industrial-level demands by top-down processing. Through controlling nucleation density on catalytic metal substrates, especially on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…with the Helmholtz free energy, as in the differences of free energies considered here the small volume dependence of the pV term largely cancels out. CVD growth of graphene on both solid and liquid Cu is typically carried out at a temperature rather close to the melting temperature of Cu of 1358 K (solid Cu CVD typically at around 1300 K 4-9 and liquid Cu CVD typically at around 1370 K [10][11][12][13][14][15][16] ). For C 2 the diffusion and rotation barrier of 0.56 eV is significantly larger than k B T at the melting temperature of Cu (0.12 eV), while the CH diffusion barrier of 0.12 eV is of equal magnitude to k B T .…”
Section: Methods Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…with the Helmholtz free energy, as in the differences of free energies considered here the small volume dependence of the pV term largely cancels out. CVD growth of graphene on both solid and liquid Cu is typically carried out at a temperature rather close to the melting temperature of Cu of 1358 K (solid Cu CVD typically at around 1300 K 4-9 and liquid Cu CVD typically at around 1370 K [10][11][12][13][14][15][16] ). For C 2 the diffusion and rotation barrier of 0.56 eV is significantly larger than k B T at the melting temperature of Cu (0.12 eV), while the CH diffusion barrier of 0.12 eV is of equal magnitude to k B T .…”
Section: Methods Assessmentmentioning
confidence: 99%
“…[4][5][6][7][8][9] Recent experimental evidence suggests that using a liquid Cu surface instead of a solid one enables the fast growth of large singlecrystalline and single-layered graphene flakes of very high structural quality. [10][11][12][13][14][15][16] While these findings are very promising for industrial-scale production of high-quality graphene samples, the reason for the improved catalytic properties of liquid Cu, and the catalytic properties of liquid metals in general, is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…So far, various growth mechanisms for self‐aligned graphene grown on liquid Cu were studied. [ 41,72,73 ] In comparison, growth of self‐aligned hBN domains is more difficult but also realized not long ago. [ 74 ] The substrate of liquid gold was chosen for the low solubility of B and N, and high diffusion of adatoms on the surface.…”
Section: Controls Of 2d Single‐crystal Growthmentioning
confidence: 99%
“…In addition, melted copper has been reported as the substrate for the growth of single-crystal SLG films. Fu and colleagues reported the seamless stitching of neighboring round graphene islands on liquid copper due to a self-rotation process on the smooth surface of liquid copper [80], while Yu and colleagues reported aligned hexagonal graphene islands grown in the temperature range 1083-1140°C, and theoretical calculations indicated that the aligned islands were driven by gas flow [81]. However, temperatures higher than the melting point of Cu, 1084.6°C, and tungsten foils, are needed to melt and support the copper.…”
Section: Single-crystal Slg Grown From Multiple Nucleimentioning
confidence: 99%